2000
DOI: 10.1016/s0168-583x(00)00192-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of electronic excitations by low-energy positrons: From finite to extended electronic systems

Abstract: This work deals with the mechanisms of electronic transitions induced by low-energy positrons. For isolated atomic systems we discuss the role of successive binary collisions, the so-called Thomas mechanisms, between the positron, the excited electron and the atomic core. Furthermore, we consider transfer processes in which one of the charged particles is trapped in a low-lying continuum state of one of the reaction participants. In the second part of the paper, we investigate the various pathways for the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…If one compares the angular (p,ep) distributions from those of (e,2e) experiments, it is also possible to separate the effect of exchange from the Coulomb correlation. The prospect of this approach was discussed in theoretical (p,ep) studies for surfaces [11,12]. In these calculations it was also shown that the (p,ep) energy distributions reveal the distinguishability between the positron and the electron.…”
mentioning
confidence: 99%
“…If one compares the angular (p,ep) distributions from those of (e,2e) experiments, it is also possible to separate the effect of exchange from the Coulomb correlation. The prospect of this approach was discussed in theoretical (p,ep) studies for surfaces [11,12]. In these calculations it was also shown that the (p,ep) energy distributions reveal the distinguishability between the positron and the electron.…”
mentioning
confidence: 99%
“…Our observations were not a priori expected, because the theoretical (p, ep) studies predict that either the electron or the positron is the more energetic particle [15,16]. Details of the valence band structure determine the outcome, but no simple argument can be put forward.…”
mentioning
confidence: 80%
“…Because of the lack of exchange in the former, it is possible to disentangle the effect of exchange from the Coulomb correlation. The prospect of this approach was discussed in theoretical (p, ep) studies for surfaces [15,16].We provide the first evidence that the positron-electron pair production at surfaces leads to features which are a consequence of distinguishable collision partners. This is not a trivial point, because inelastic processes before or after the positron collision may mask the anticipated effect.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The differences and common features of electron emission from metallic surfaces upon the impact of low energy positrons or electrons has been discussed by Berakdar [13]. Berakdar also first considered theoretically positron-electron pair emission upon the impact of low energy positrons and diffraction of the positron-electron pair, illustrating how distinguishability of the electron and positron leads to differences between the angular distribution of electronpositron pair emission upon positron impact and electronelectron pair emission upon electron impact.…”
Section: Introductionmentioning
confidence: 99%